The role of social networking sites in improving UiTM's undergraduates' academic learning process / Nur Amalina Zaharudin - Zaharudin, Nur Amalina (2014)
In the 21st century, education technologies such as multimedia technology have been used rapidly, corresponding with the globalization era. Technology has a great impact on the education system, for examples it allows students to expand their knowledge, have better interaction with each other as well as increase their engagement and motivation in learning process. Education today is exposed to the competitive environment with the adaptation of the current technology era of high speed Internet connection and instant updating. Before this, we only have traditional face-to-face learning environment between students and teachers. Nowadays, learning with the aid of Internet has become an inclination in educational system. Thus, this research tend to investigate undergraduate students' perception towards social networking sites in their academic learning process as well as to provide an overview on either social networking sites can help UiTM's undergraduate learners to improve their academic learning process and the effects of social networking services on their academic learning process. 100 undergraduate students from Universiti Teknologi MARA and INTEC in Shah Alam were involved. Quantitative approach was employed with questionnaires used as the instruments. Findings revealed that students have positive views and opinions towards social networking sites in their academic learning. Despite the positive perceptions, students also agreed that social networking sites have positively effects in their academic learning and the used of social networking services have actually affects positively in their learning process.